Experimental and numerical investigation on buckling and post-buckling of a 3000 m Subsea Separator. (April 2017) - Ge, Jiuhao; Li, Wei; Chen, Guoming; Li, Xiumei; Ruan, Caitian; Zhang, Shenyan
Abstract: Ultra-deep water subsea separator, bearing huge external pressure, is a key equipment of subsea production in the offshore petroleum industry. In this paper, the buckling and post-buckling behavior of a 3000 m subsea separator is analyzed by numerical and experimental methods. In simulation, the nonlinear global buckling analysis, including nonlinear material and initial imperfections, is performed to analyze the global buckling behavior of the ultra-deep water subsea separator. In the experiment, a two circumferential lobe mode is present and the buckling deformation is asymmetrical. The comparison of numerical and experimental results has shown the numerical results that indicate a similar behavior and deformation mechanism. The nonlinear global buckling analysis proposed in this paper can numerically simulate the buckling process of the ultra-deep subsea separator with good accuracy. Finally, the influences of length to diameter ratio, ovality, and support on global buckling are researched. Highlights: The buckling and post-buckling behavior of a 3000 m subsea separator is analyzed by numerical and experimental methods. The nonlinear global buckling analysis is performed to analyze the global buckling behavior of the ultra-deep water subsea separator. In the experiment, a two circumferential lobe mode is present and the buckling deformation is asymmetrical. The nonlinear global buckling analysis proposed can numerically simulate the buckling process of the ultra-deep subsea separator with good accuracy.